2013
DOI: 10.5194/acp-13-11803-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of seasonal and regional variability in biogenic VOC emissions on surface ozone in the Pearl River delta region, China

Abstract: Abstract. This study investigated the impacts of seasonal and regional variability in biogenic volatile organic compounds (BVOCs) on surface ozone over the Pearl River delta (PRD) region in southern China in 2010 with the WRFChem/MEGAN (Weather Research and Forecasting coupled with Chemistry/Model of Emissions of Gases and Aerosols from Nature) modeling system. Compared to observations in the literature and this study, MEGAN tends to predict reasonable BVOC emissions in summer, but may overestimate isoprene em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 69 publications
3
45
1
Order By: Relevance
“…Emmerson et al (2016) found ratios close to 1 for observed levels in the Sydney basin. This is in contrast to a ratio of 0.18 found in boreal forests dominated by monoterpenes (Spirig et al, 2004), and to a ratio of 26.4 in deciduous Michigan forests dominated by isoprene (Kanawade et al, 2011). SOA formation is inhibited in regions where isoprene dominates, however it is not known what impact a carbon ratio of one will have.…”
Section: Spatial Distribution Of Emissionscontrasting
confidence: 47%
See 1 more Smart Citation
“…Emmerson et al (2016) found ratios close to 1 for observed levels in the Sydney basin. This is in contrast to a ratio of 0.18 found in boreal forests dominated by monoterpenes (Spirig et al, 2004), and to a ratio of 26.4 in deciduous Michigan forests dominated by isoprene (Kanawade et al, 2011). SOA formation is inhibited in regions where isoprene dominates, however it is not known what impact a carbon ratio of one will have.…”
Section: Spatial Distribution Of Emissionscontrasting
confidence: 47%
“…One of the most commonly used algorithms for estimating BVOC emission rates was proposed by Guenther et al (1991Guenther et al ( , 1993Guenther et al ( , 1995 and Guenther (1997) providing the basis for the Model of Emissions of Gases and Aerosols from Nature, MEGAN (Guenther et al, 2006(Guenther et al, , 2012. MEGAN has been used to estimate the BVOC emissions within many atmospheric chemistry models (Heald et al, 2008;Pfister et al, 2008;Stavrakou et al, 2009Stavrakou et al, , 2014Emmons et al, 2010;Millet et al, 2010;Situ et al, 2013;Kim et al, 2014;Tilmes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By using the Weather Research and Forecasting coupled with Chemistry (WRF-Chem)/ Model of Emissions of Gases and Aerosols from Nature (MEGAN) model, Situ et al (2013) estimated the impacts of seasonal variations in BVOCs on surface-layer O 3 over the Pearl River Delta region for year 2010 and reported that the impact of BVOC emissions on the surface ozone peak was about 10 ppbv (3 ppbv) on average with a maximum value of 34 ppbv (24.8 ppbv) in summer (autumn), as the concentrations simulated with BVOC emissions were compared with those simulated without BVOC emissions. By using the GEOS-Chem/MEGAN model, Fu and Liao (2012) reported that the interannual variations in BVOCs over 2001Á2006 led to differences in simulated summertime surface-layer O 3 and SOA concentrations in China by 2Á5%.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates from Zare et al (2014) found BVOC to be the most significant contributor to ozone formation over land areas in the Northern Hemisphere enhancing the mixing ratio by about 11 %. In the Pearl River Delta in China (Situ et al, 2013) ozone is sensitive to the BVOC levels particularly in urban areas. At a regional European scale, biogenic emissions increase O 3 locally, while reducing PM 2.5 levels (Tagaris et al, 2014).…”
Section: Role Of Biogenics In the Formation Of Ozonementioning
confidence: 99%